Sources of paratyphoid Salmonella in the production chain of broilers in the Northern mesoregion of Maranhão State, Brazil - Brito, Daniela Aguiar Penha (2019)
Paratyphoid Salmonella significantly impacts modern poultry farming, because it is one of the main causes of foodborne diseases in the world. Efforts have been made by the government and poultry industry to reduce the existence of Salmonella in the entire poultry production chain through sanitary programs. The aim of this work was to investigate the occurrence of Salmonella spp. and its serovars in environmental sources of production, poultry, and carcasses slaughtered in an artisanal manner in the northern mesoregion of Maranhão State, Brazil. A total of 520 samples were collected, comprising drag swabs (n = 60), prope (n = 60), cecal feces (n = 60), feed of feeder (n = 60), and cloacal swabs (n = 100) of poultry sent for slaughter, and newly slaughtered carcasses (n = 180). The samples were subjected to culture and isolation of Salmonella spp. and serotyping. The occurrence of the genus Salmonella was 25.0% (15/60) in drag swabs, 16.6% (10/60) in prope, 1.7% (1/60) in cecal feces, absent (0/60) in the feed, 7% (7/100) in cloacal swabs, and 48.9% (88/180) in poultry carcasses. Fifteen Salmonella enterica serovars were identified in the samples, with the highest occurrence in the Schwarzengrund (28.09%; 34/121), Albany (19.83%; 24/121), Enteritidis (7.43%; 9/121), and Heidelberg (7.43%; 9/121). Salmonella ser. Schwarzengrund showed higher predominance in the poultry production chain, with greater isolation in carcass samples (34 isolates), while Salmonella ser. Enteritidis had the highest occurrence in the initial production chain. The results of our study indicate the need to implement sanitary control in farms for paratyphoid salmonella and that artisanal poultry slaughter can increase bacterial dissemination in the final product, representing a public health risk.